Molecular Biology of the Cell. The Problems Book - Wilson J. John (New York, Garland Science, 2015)
The Problems Book helps students appreciate the ways in which experiments and simple calculations can lead to an understanding of how cells work. This is accomplished by introducing the experimental foundation of cell and molecular biology. Each chapter reviews key terms, tests for understanding basic concepts and poses research-based problems. This book is designed to correspond with the first 20 chapters of Molecular Biology of the Cell, Sixth Edition.